2012
DOI: 10.1038/onc.2012.27
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of NuSAP in recurrent prostate cancer is mediated by E2F1

Abstract: Increasing evidence suggests that prostate cancer is over diagnosed and over treated, and prognostic biomarkers would aid in treatment selection. To define prognostic biomarkers for aggressive prostate cancer, we carried out gene expression profiling of 98 prostate tumors and 52 benign adjacent prostate tissue samples with detailed clinical annotation. We identified 28 transcripts significantly associated with recurrence after radical prostatectomy including NuSAP, a protein that binds DNA to the mitotic spind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
157
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(162 citation statements)
references
References 47 publications
5
157
0
Order By: Relevance
“…The Gulzar dataset (Gulzar et al, 2013) suggests that PCa recurrence is higher in patients with low PMEPA1 expression, compared to those with high PMEPA1 (Fig 3F). Despite the separation between the populations after 2 years, the difference was not significant, which could be due to the small number of patients (n = 67).…”
Section: Resultsmentioning
confidence: 97%
“…The Gulzar dataset (Gulzar et al, 2013) suggests that PCa recurrence is higher in patients with low PMEPA1 expression, compared to those with high PMEPA1 (Fig 3F). Despite the separation between the populations after 2 years, the difference was not significant, which could be due to the small number of patients (n = 67).…”
Section: Resultsmentioning
confidence: 97%
“…In addition, mitotic dysfunction by deregulated E2F1 and the consequent onset of oncogenesis are also emerging. E2F1 also induces increased expression of the mitotic proteins PTTG1 and NuSAP in pituitary and prostate tumors, respectively (54,55). Defects in SAC function may result in CIN and aneuploidy, which are hallmarks of cancer (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…In a relevant study, a Kaplan-Meier plot revealed the significant association between higher WHSC1 expression and disease relapse in 2 separate patient cohorts (using data sets GSE21032 and GSE40272; Figure 1B and refs. 4,39). To further assess the clinical relevance of WHSC1 in PCa, we performed IHC staining with a validated antibody against WHSC1 on an Asian radical prostatectomy cohort (40), a tumor tissue microarray (TMA) composed of 118 patient specimens (Supplemental Table 2).…”
Section: Whsc1 Is Associated With Human Metastatic Pcamentioning
confidence: 99%